FORMATION OF A SCIENTIFIC AND GENERAL-CULTURAL OUTLOOK IN THE EDUCATIONAL PROCESS - Boliqulova Madinabonu; Shamuradova Naima (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The formation of scientific and cultural worldviews in the educational process has a significant impact on students’ personality, culture, and intellectual development. Scientific worldview primarily encompasses logical thinking, problem analysis, and the use of scientific methodologies. On the other hand, cultural worldview ensures an understanding  of  social,  cultural,  and  ethical  values.  The  interconnection  of  these processes  serves  to  enhance  the  quality  of  education,  support  students’  personal development, and bring about positive changes in society.